Addressing Disparities in Physician Access to Information in Support of Evidence-based Practice. Issue 7 (7th June 2021) - Aspinall, Erinn E.; Hunt, Shanda L.; Theis-Mahon, Nicole R.; Chew, Katherine V.; Olawsky, Evan
ABSTRACT: The purpose of this study is to determine if Minnesota physicians have access to information resources needed to support evidence-based practice (EBP), which supports a culture of safety and patient-centered care. A survey was used to determine Minnesota physicians' need for, and access to, evidence-based clinical information. A total of 877 responses (6.4% response rate) were included in the data analysis. Participants spent 24 min daily seeking answers to clinical questions and averaged 4.41 questions per day that could not be immediately answered. Physicians reported high levels of information needs met (85.8%), though they reported limited access to drug resources, citation databases, systematic reviews, and full-text books and articles. Results also showed use of unreliable sources to support decision-making. A key finding was the extent to which workplace affiliation broadens disparities in information access. National and regional approaches can work to support EBP by reducing the information gap caused by workplace affiliation and other barriers. Further research should be done to identify partnerships, funding, infrastructure, and support to address these gaps.